Autoimmune progesterone dermatitis manifesting as generalized fixed drug eruption - Juan Eduardo Carrasco-Zuber; Sergio Álvarez-Véliz; Catherina Moll-Manzur; Sergio González-Bombardiere (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Autoimmune progesterone dermatitis is an uncommon, poorly recognized and under-diagnosed catamenial dermatosis associated with hypersensitivity reactions to progestagens. Most cases manifest as urticaria, eczema or erythema multiforme-like. A 26-year-old woman developed violaceous plaques on the groin and abdomen, 4 days after a spontaneous abortion resolved with uterine curettage. The lesions recurred once monthly at the same sites, mimicking a fixed drug eruption. Although the histopathology was compatible with fixed drug eruption, positive intradermal testing and symptomatic improvement after using oral contraceptive pills gave us a clue to the diagnosis.